Comparison of thermal fatigue behaviour and microstructure of different hot work tool steels processed by biomimetic couple laser remelting process. (1st April 2013) - Meng, C; Zhou, H; Tong, X; Cong, D L; Wang, C W; Ren, L Q
<x xml:space="preserve">Abstract</x> For comparing the enhancement degree of the thermal fatigue behaviour of different hot work tool steels processed by laser remelting, three kinds of hot work tool steels (HHD, H13 and HD steels) were selected to investigate the effect of biomimetic coupled laser remelting process on the thermal fatigue behaviour. The results showed that biomimetic non-smooth samples had better thermal fatigue behaviour compared to untreated samples, the biomimetic non-smooth sample of HHD had the optimum thermal fatigue behaviour. Moreover, before and after thermal fatigue testing, the microhardness and microstructure of biomimetic non-smooth units and parent materials have been investigated. The results showed that biomimetic non-smooth sample of HHD had the highest resistance of thermal cycles softening among the biomimetic non-smooth samples. The microstructures observation indicated that the microstructures of parent materials were a substantial amount of the carbides coarsening while the microstructures of biomimetic non-smooth units were coarse grains after thermal fatigue test.